Antecedents of Audit Fee Paid by Trade and Service Companies that Listed in BEI for 2019-2020 - Andrew Christian Sudjono (AIBPM Publisher, 2022)
The audit process is one of the tools used to handle the agency problem that may happen within a company. The audit process may become the most effective tool that only auditors that can execute the audit process, whether the internal auditor that works within the company or the external auditor that performs the audit process on behalf of the public accounting firm. To complete the audit process, each company will have to pay the audit fee for the external auditor and public accounting firm. This research analyzed the factors that may affect companies’ audit fees, from the board of commissioners size, audit complexity, firm risk, and the audit firm size being used by the public companies. The multiple linear regression analysis results show that all of these variables are found to affect the audit fee that was paid by the trade and service companies. Lastly, all the factors were found to affect the audit fee simultaneously. As an effort for companies to reduce the audit fee, they need to be concerned about these factors. Keywords: Audit Fee, Audit Complexity, Firm Risk, Public Accounting Firm’s Size, The Board of Commissioners Size